Aspek Hukum Fasilitas Ruang Laktasi pada Pusat Perbelanjaan (Mall) di Kota Medan - Kartika, Arie; Wahyuni, Windy Sri; Harahap, Dessy Agustina (TIN: Terapan Informatika Nusantara, 2021)
The state is obliged to ensure that health services are provided for women, especially family planning (KB) services, pregnancy, childbirth, postpartum or exclusive breastfeeding. It cannot be denied that until now there are still many offices / companies and Malls that ignore the existence of lactation rooms. Whereas the obligation of work organizers to provide lactation space has been regulated in the Republic of Indonesia Minister of Health Regulation Number 15 of 2013. The regulation of procedures for providing breastfeeding space aims to provide protection to mothers in exclusive breastfeeding and fulfill children's rights to receive exclusive breastfeeding. The provision of this breastfeeding corner facility is devoted to meeting the needs of mothers and babies who still have to breastfeed, and at the same time aims to increase exclusive breastfeeding for babies as one of the main nutrients. This step also plays a role in reducing infant mortality, because the baby's immunity will increase through breast milk. However, the reality on the ground says differently. So the problem is what is the legal arrangement for lactation room facilities in shopping centers (Malls) in Medan City? and What are the legal consequences for the unavailability of lactation space in shopping centers (Malls) in Medan City? This type of research used in this research is normative legal research. Normative legal research is also called doctrinal legal research because this research is carried out by analyzing written laws from library materials or secondary data which are better known as names and reference materials in the field of law or reference materials in the field of law